Sensing Behavior Study of Cobalt Zinc Ferrite Nanoparticles Against Acetone in Various Temperatures - Alireza Ghasemi; Hamid Reza Ebrahimi; Mohsen Ashourian; Hassan Karimi Maleh; Gholam Reza Amiri (Majlesi Journal of Electrical Engineering)
The Cobalt zinc ferrite nanoparticles with diameters less than 20 nm were prepared. By XRD (X-ray diffraction), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) the morphology and the structure of this ferrite were studied. The X-ray analysis shows the formation of manganese zinc ferrite in the spinel phase. SEM photograph is shown the spherical shape of nanoparticles. And the TEM conï¬rmed the nanoscale dimensions of the samples. The cobalt zinc ferrite nanoparticles crystallite sizes, calculated by the Debye-Scherer formula, were found near 13 nm. The sensitivity properties of this ferrite are investigated in a totally isolated plexi glass box. By injecting 1 mL of liquid and vaporizing it, we will have 200 ppm concentration of each sample in this box. Then the injected vapored sample in this box is exposed to the ferrite. After this step, the conductivity of the ferrite in a closed circuit was changed. By changing the sample type, amount of this conductivity was varied. Six gases were tested in this project: ethanol, nitrile alcohol, dimethyl formamide, carbon tetrachloride, acetonitrile, and acetone. Among these samples, the carbon tetrachloride had the best sensitivity performance. Finally, the sensor equation for carbon tetrachloride was extracted by applying different concentrations of it from 20 to 200 ppm.